Clinopodium serpyllifolium subsp. sirnakense (Lamiaceae), a new taxon from south-eastern Anatolia, Turkey - Fırat, Mehmet; Akçiçek, Ekrem; Kaya, Ayla (Phytotaxa, 2015)
Clinopodium serpyllifolium subsp. sirnakense (Lamiaceae) is described as a new subspecies from south-eastern Anatolia, Turkey. It is considered morphologically similar to Clinopodium serpyllifolium subsp. brachycalyx, from which it differs in indumentum, calyx characters and mericarp surface. Detailed illustrations are provided along with a distribution map, an IUCN ranking and notes on taxonomic affinities.